Phytochemistry and Biological Activity of Medicinal Plants in Wound Healing: An Overview of Current Research - Stefania Vitale; Sara Colanero; Martina Placidi; Giovanna Di Emidio; Carla Tatone; Fernanda Amicarelli; Anna Maria D’Alessandro (Molecules, 2022)
Wound healing is a complicated process, and the effective management of wounds is a major challenge. Natural herbal remedies have now become fundamental for the management of skin disorders and the treatment of skin infections due to the side effects of modern medicine and lower price for herbal products. The aim of the present study is to summarize the most recent in vitro, in vivo, and clinical studies on major herbal preparations, their phytochemical constituents, and new formulations for wound management. Research reveals that several herbal medicaments have marked activity in the management of wounds and that this activity is ascribed to flavonoids, alkaloids, saponins, and phenolic compounds. These phytochemicals can act at different stages of the process by means of various mechanisms, including anti-inflammatory, antimicrobial, antioxidant, collagen synthesis stimulating, cell proliferation, and angiogenic effects. The application of natural compounds using nanotechnology systems may provide significant improvement in the efficacy of wound treatments. Increasing the clinical use of these therapies would require safety assessment in clinical trials.